Commercialism and Identity Politics in New York's Chinatown. (November 2015) - Li, Chuo
After World War II, a remarkable, self-conscious process of community building has taken place in U.S. Chinatowns, especially when the institution of the Immigration and Nationality Act of 1965 led to the eventual abolition of Asian quotas. New York's Chinatown presents a case study of the postwar transformation that was related to both the global geopolitical changes and domestic urban economic restructuring. With the liberation of immigration laws, the Chinese population in New York has been continuously growing and becoming diversified. Illustrating the way notions of identity and heritage function to (re)assert spatial identity, the article examines the contested process of landscape construction in New York's Chinatown and the underpinning social agendas, cultural and political implications in the process of identity-making.